The Distributional Effects of Tobacco Taxation : The Evidence of White and Clove Cigarettes in Indonesia - Fuchs, Alan (World Bank, Washington, DC, 2018)
Despite the well-known positive impact of tobacco taxes on health outcomes, policy makers hesitate to use them because of their possible regressive effect, that is, poorer deciles are proportionally more negatively affected than richer ones. Using an extended cost-benefit analysis to estimate the distributional effect of white and clove cigarettes in Indonesia, this study finds that the long-run impact may be progressive. The final aggregate effect incorporates the negative price effect, but also changes in medical expenditures and in additional working years. The analysis includes estimates of the distributional impacts of price rises on cigarettes under various scenarios using 2015–16 Indonesia National Socioeconomic Surveys. One contribution is to quantify the impacts by allowing price elasticity's to vary across consumption deciles. Overall, clove cigarette taxes exert an effect that depends on the assumptions of conditional price elasticity. If the population is more responsive to tobacco price changes, then people would experience even more gains from the health and work benefits. More research is needed to clarify the distributional effects of tobacco taxation in Indonesia.